2004
DOI: 10.1111/j.1466-822x.2004.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Rarity, commonness, and patterns of species richness: the mammals of Mexico

Abstract: Aim To determine whether rare or common species contribute most to overall patterns of spatial variation in extant species richness. Location Mexico.Methods Using data on the distribution of mammal species across Mexico at a quarter degree resolution, we ranked species from the most widespread to the most restricted (common-to-rare) within the study area, and from the most restricted to the most widespread (rare-to-common), and generated a sequence of patterns of species richness for increasing numbers of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
3
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 32 publications
8
59
3
3
Order By: Relevance
“…Although species richness has been considered a good surrogate of biodiversity in many studies (Real et al 1993;Araújo 1999;Maes et al 2005), there are some authors who have shown that species richness is more related with the distribution of generalist species than to the distribution of rare ones (Vázquez and Gaston 2004). However, the majority of the fuzzy favourability hotspots for mammals obtained in this study coincide with those of fuzzy mammal rarity in Andalusia (Real et al 2006b).…”
Section: Surrogates Of Biodiversitycontrasting
confidence: 45%
“…Although species richness has been considered a good surrogate of biodiversity in many studies (Real et al 1993;Araújo 1999;Maes et al 2005), there are some authors who have shown that species richness is more related with the distribution of generalist species than to the distribution of rare ones (Vázquez and Gaston 2004). However, the majority of the fuzzy favourability hotspots for mammals obtained in this study coincide with those of fuzzy mammal rarity in Andalusia (Real et al 2006b).…”
Section: Surrogates Of Biodiversitycontrasting
confidence: 45%
“…It has been shown with large-scale data that common species drive species richness patterns (Jetz and Rahbek 2002; Lennon et al 2004;Vá zquez and Gaston 2004), and that the richness of common species is more closely related to environmental variation than that of rare species (Jetz and Rahbek 2002;Kreft et al 2006;Rahbek et al 2007). However, the generality of such conclusions remains to be addressed with other organism groups and across metacommunities.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, including those of British breeding birds, that have grouped species into either abundance or range size classes have also found that the commonest species exhibit the strongest species-energy relationships ( Jetz & Rahbek 2002;Ruggiero & Kitzberger 2004;Vázquez & Gaston 2004;Evans et al 2005b,c). The MIH describes the relationship between extinction risk and local population size, which may appear to contrast with our use of national Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These predictions can be tested by assessing how the richness of different species groups, such as common and rare species, respond to energy availability ( Jetz & Rahbek 2002;Ruggiero & Kitzberger 2004;Vázquez & Gaston 2004;Evans et al 2005b,c). An alternative and complementary approach, that as far as we are aware has not been previously used, is based on the principle that species richness results from the summation of occurrence data for each species in the focal assemblage.…”
Section: Introductionmentioning
confidence: 99%